Transforming a General Hospital to an Infectious Disease Hospital for COVID-19 Over 2 Weeks - Pandey, Navin; Kaushal, Vipin; Puri, Goverdhan Dutt; Taneja, Sunil; Biswal, Manisha; Mahajan, Pranay; Guru, Rashmi Ranjan; Malhotra, Pankaj; Sehgal, Inderpaul Singh; Dhooria, Sahajal; Muthu, Valliappan; Agarwal, Ritesh (Frontiers in Public Health, 2020)
We must accept the inevitability of pandemics like the coronavirus infectious disease (COVID)-19. Healthcare organizations must be ready with their contingency plans for managing these large number of patients with contagious infectious disease. It would be ideal that every large hospital has a facility that can function as a high-level isolation unit. An isolation unit ensures that the healthcare staff and the hospital are equipped to deal with infectious disease pandemics. Unfortunately, such facilities do not exist in several hospitals, especially in resource-limited settings. In such a scenario, healthcare setups need to convert their existing general setup into an infectious disease facility. Herein, we describe our experience in transforming a general hospital into a functional infectious disease isolation unit.